Implementation of Musyarakah Financing On Micro, Small, and Medium Enterprises (MSME): Solutions for Regional Economic Recovery Post Covid-19 Pandemic - Purnamasari, Femei; Susanti, Yeni; Rosilawati, Weny (Universitas Trunojoyo Madura, 2025)
This research aims to analyze the implementation of Musyarakah financing at Bank Syariah Indonesia (BSI) in the Micro, Small, and Medium Enterprises (MSME) sector in the cities of Bandar Lampung and Metro as a solution for regional economic recovery post-Covid-19 pandemic and the development of MSMEs after receiving Musyarakah financing.The research method applied is a descriptive qualitative method with a field research approach, where the data collection process is carried out using observation, interviews, and documentation methods as tools to obtain information about the implementation of Musyarakah financing.The results of this study indicate that the implementation of Musyarakah financing by Islamic Banks serves as a solution for the post-Covid-19 economic recovery in the region and is capable of increasing the income of MSMEs.